Qualitative research and evaluation in physical education and sport pedagogy - Richards, Kevin Andrew; Hemphill, Michael A.; Wright, Paul M. (Professor of kinesiology and physical education)
"A practically-focused introductory qualitative methods text specific to physical education and activity to guide graduate students and early career researchers through the design, conduct, and reporting of qualitative research studies with specific references to the challenges and possibilities of the field"
Revisiting the goodness of qualitative research -- Historical evolution of qualitative research within physical education and sport pedagogy -- Philosophies, paradigms, and theoretical orientations in qualitative research -- Qualitative research design principles -- Improvement science to address practical realities with qualitative research -- Applying qualitive research design principles in physical education and sport -- Community-engaged scholarship methods and the ethics of qualitative research -- The role of theory in guiding qualitative design decisions -- Qualitative interviewing approaches and strategies -- Fieldwork and observation in physical activity environments -- Using documents and artifacts : document analysis in qualitative research -- Visual methodologies and emerging qualitative approaches -- Mixed methods in physical education and physical activity -- Interpretivist approaches to qualitative analysis -- Revisiting and reframing a collaborative approach to qualitative data analysis -- The sort and sift, think and shift analysis method -- Writing up and discussing the results of qualitative research -- Activist research in physical education and physical activity settings -- Practitioner-driven research methods -- Using qualitative methods working with disabled people -- Using qualitative research as part of a social justice agenda -- Case study methodology in physical education and sport pedagogy -- Conclusion, synthesis, and future directions.
MS Salazar (Recommending faculty) AY2022-2023
MS Salazar (Recommending faculty) AY2022-2023
Includes bibliographical references and index.
Keywords: Physical education and training -- Research -- Methodology; Qualitative research